Sociological Roots of the Emergence of Terrorism in Indonesia: An Interdisciplinary Approach - Mappasessu Mappasessu; Kurniati Kurniati; Misbahuddin Misbahuddin (Journal of Strafvordering Indonesian, 2024)
This study aims to analyze the sociological measurement of the emergence of terrorism in Indonesia, as well as the development of terrorism and its prevention. The purpose of the research is to look at the sociological roots in more detail to find more comprehensive steps in preventing terrorism in Indonesia. This study uses qualitative description. The research method uses library research which obtains secondary data including literature books, laws and regulations, official documents, and other relevant data. In this writing, the author uses a sociological history approach. The result of this paper is that terrorism has many dimensions, namely the local dimension, the regional dimension, and the global dimension to unravel the sociological roots of the emergence of terrorism in Indonesia, then the overcoming steps need cooperation from all parties, the government, the community, and the international world because the overcoming action is not by using repression so that it can violate human rights, but also using a socio-cultural approach by inviting all components including the so that the seeds of terrorism that exist in society can be minimized, and cut off the roots of its development to grow radicalism in common life.